Total evidence phylogeny of platyrrhine primates and a comparison of undated and tip-dating approaches. Issue 174 (January 2023) - Beck, Robin M.D.; de Vries, Dorien; Janiak, Mareike C.; Goodhead, Ian B.; Boubli, Jean P.
Abstract: There have been multiple published phylogenetic analyses of platyrrhine primates (New World monkeys) using both morphological and molecular data, but relatively few that have integrated both types of data into a total evidence approach. Here, we present phylogenetic analyses of recent and fossil platyrrhines, based on a total evidence data set of 418 morphological characters and 10.2 kilobases of DNA sequence data from 17 nuclear genes taken from previous studies, using undated and tip-dating approaches in a Bayesian framework. We compare the results of these analyses with molecular scaffold analyses using maximum parsimony and Bayesian approaches, and we use a formal information theoretic approach to identify unstable taxa. After a posteriori pruning of unstable taxa, the undated and tip-dating topologies appear congruent with recent molecular analyses and support largely similar relationships, with strong support for Stirtonia as a stem alouattine, Neosaimiri as a stem saimirine, Cebupithecia as a stem pitheciine, and Lagonimico as a stem callitrichid. Both analyses find three Greater Antillean subfossil platyrrhines ( Xenothrix, Antillothrix, and Paralouatta ) to form a clade that is related to Callicebus, congruent with a single dispersal event by the ancestor of this clade to the Greater Antilles. They also suggest that the fossil Proteropithecia may not be closely related to pitheciines, and that all known platyrrhines older than the Middle Miocene are stem taxa. Notably, the undated analysis found the Early Miocene Panamacebus (currently recognized as the oldest known cebid) to be unstable, and the tip-dating analysis placed it outside crown Platyrrhini. Our tip-dating analysis supports a late Oligocene or earliest Miocene (20.8–27.0 Ma) age for crown Platyrrhini, congruent with recent molecular clock analyses.